bonsoir,

a= 3t+(2T(puissance 2)+9) - (-9t+t(puissance2))

b = x - (11-x(puissance2))+(12x-3)

c=2y(puissance2)-(3y-6y(puissance2)+(-5y+9)

d=7z+(5z (puissance2)-5z)-(2z-3)


Merci beaucoup à celui ou celle qui l'aura réussi .

1

Réponses

2012-12-10T20:16:22+01:00

A = 3t +(2t puissance²) +9 - (-9t + t puissance²)

A = 3t 4t² +9 +9t +t²

A = 5t² +12t

B= x -(11x puissance²) + (12x -3)

B= x-121 x² +12x -3

B= -121 x² +13x -3

C = 2y(puissance²) - ( 3y -6y puissance²) + (-5y +9)

C= 4y²  - 3y +36y² -5y +9

C= 40 y² -8y +9

D= 7z +(5z puissance²) -5z) -(2z -3)

D= 7z +25z² -5z -2z + 3

D= +25z² +3

 

Je pense avoir fait le max . Bon courage